PENGELOLAAN PENGETAHUAN DI SEKOLAH MENENGAH PERTAMA ISLAM TERPADU AL-ANIS KARTASURA - arifiani, Anita; Bahtiar, Yusuf (Universitas Negeri Jakarta, 2023)
ABSTRACT This research aims to analysis how knowledge is managed at the Al-Anis Kartasura (Integrated Islamic Junior High School) educational Institution regarding the dimensions of knowledge management such as knowledge reaction, knowledge storage and knowledge distribution. The research method used is a qualitative research method with data collection techniques through observation and interview. The results of this research indicate that Al-Ansi IT Junior High School has the quality of education in the adequate category and needs to evaluate and improve the quality of education with consistent knowledge management, effective and inovatif. Keywords: Management; Knowledge; Production; Storage; Distribution